Effect of manganese doping on the hyperthermic profile of ferrite nanoparticles using response surface methodology. Issue 28 (7th May 2021) - Gupta, Ruby; Tomar, Ruchi; Chakraverty, Suvankar; Sharma, Deepika
Abstract : Magnetic hyperthermia-based cancer therapy mediated by magnetic nanomaterials is a promising antitumoral nanotherapy, owning to its power to generate heat under the application of an alternating magnetic field. Abstract : Magnetic hyperthermia-based cancer therapy mediated by magnetic nanomaterials is a promising antitumoral nanotherapy, owning to its power to generate heat under the application of an alternating magnetic field. However, although the ultimate targets of these treatments, the heating potential and its relation with the magnetic behavior of the employed magnetic nanomaterials are rarely studied. Here we provide a bridge between the heating potential and magnetic properties such as anisotropy energy constant and saturation magnetization of the nano-magnets by simultaneous investigation of both hyperthermia and magnetism under a controlled set of variables given by response surface methodology. In the study, we have simultaneously investigated the effect of various synthesis parameters like cation ratio, reaction temperature and time on the magnetic response and heat generation of manganese-doped ferrite nanomaterials synthesized by a simple hydrothermal route. The optimum generation of heat and magnetization is obtained at a cationic ratio of approximately 42 at a temperature of 100 °C for a time period of 4 h. The optimized nanomaterial was then evaluated for in vitro magnetic hyperthermia application for cancer therapy against glioblastoma in terms of cell viability, effect on cellular cytoskeleton and morphological alterations. Furthermore, the correlation between the magnetic properties of the synthesized nanomaterial with its hyperthermia output was also established using K . V . M s variable where K, V and M s are the anisotropy energy constant, volume, and saturation magnetization of the nanomaterial respectively. It was found that the intensity of heat generation decreases with an increase in K . V . M s value, beyond 950 J emu g −1 .